A photoanode with hierarchical nanoforest TiO2 structure and silver plasmonic nanoparticles for flexible dye sensitized solar cell - Brishty Deb Choudhury (Nature Portfolio, 2021)
Abstract Due to unique photovoltaic properties, the nanostructured morphologies of TiO2 on flexible substrate have been studied extensively in the recent years for applications in dye sensitized solar cells (DSSCs). Microstructured electrode materials with high surface area can facilitate rapid charge transport and thus improve the light-to-current conversion efficiency. Herein we present an improved photoanode with forest like photoactive TiO2 hierarchical microstructure using a simple and facile hydrothermal route. To utilize the surface plasmon resonance (SPR) and hence increase the photon conversion efficiency, a plasmonic nanoparticle Ag has also been deposited using a very feasible photoreduction method. The branched structure of the photoanode increases the dye loading by filling the space between the nanowires, whereas Ag nanoparticles play the multiple roles of dye absorption and light scattering to increase the light-to-current conversion efficiency of the device. The branched structure provides a suitable matrix for the subsequent Ag deposition. They improve the charge collection efficiency by providing the preferential electron pathways. The high-density Ag nanoparticles deposited on the forest like structure also decrease the charge recombination and therefore improve the photovoltaic efficiency of the cells. As a result, the DSSC based on this novel photoanode shows remarkably higher photon conversion efficiency (ηmax = 4.0% and ηopt = 3.15%) compared to the device based on pristine nanowire or forest-like TiO2 structure. The flexibility of the device showed sustainable and efficient performance of the microcells.